2006
DOI: 10.1177/117727190600100017
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive Protein in Patients with Metastatic Clear Cell Renal Carcinoma: An Important Biomarker for Tumor-associated Inflammation

Abstract: Two consecutive multi-center phase II trials were designed to prove the hypothesis, whether therapeutic modeling of tumor-associated inflammatory processes could result in improved tumor response.Therapy in both trials consisted of low-dose capecitabine 1g/m2 twice daily p.o. for 14 days, every 3 weeks, day 1+, and rofecoxib 25 mg daily p.o., day 1+ (from 11/04 etoricoxib 60 mg daily instead) plus pioglitazone 60 mg daily p.o., day 1+. In study II low-dose IFN-α 4.5 MU sc. three times a week, week 1+, was adde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 51 publications
0
29
0
Order By: Relevance
“…But in a subsequent study, IFN-seemed to act complementary tilting the systems biology of the tumor to a measurable response with inflammation control in all patients with initially elevated CRP (C reactive protein) levels [30]. But in a subsequent study, IFN-seemed to act complementary tilting the systems biology of the tumor to a measurable response with inflammation control in all patients with initially elevated CRP (C reactive protein) levels [30].…”
Section: Role Of Ppar / In the Regulation Of Antitu-moral Immunitymentioning
confidence: 94%
“…But in a subsequent study, IFN-seemed to act complementary tilting the systems biology of the tumor to a measurable response with inflammation control in all patients with initially elevated CRP (C reactive protein) levels [30]. But in a subsequent study, IFN-seemed to act complementary tilting the systems biology of the tumor to a measurable response with inflammation control in all patients with initially elevated CRP (C reactive protein) levels [30].…”
Section: Role Of Ppar / In the Regulation Of Antitu-moral Immunitymentioning
confidence: 94%
“…In metastatic RCCC, we selected in a second consecutive trial an anti-inflammatory approach with presumably enhanced anti-inflammatory capacity: pioglitazone, coxib, and additionally interferon-alpha [ 12 ]. In HRPC, a combination of two activators of nuclear transcription factors (pioglitazone and dexamethasone) has been introduced [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Pathological reactions caused by a stress response to surgical operations, such as immunosuppression and metabolic disturbances, are related to tumour necrosis, nutritional status and prognosis to some degree (15,16). It has been widely shown that changes in serum CRP, IL-6 and T lymphocyte counts in peripheral blood are indices of immune response after tumour operation (17,18).…”
Section: Discussionmentioning
confidence: 99%